Comparative Analysis of the Physicochemical and Microbiological Properties of Lactobacillus plantarum and Lactobacillus acidophilus Fermented Milk with Prebiotic Kepok Banana (Musa acuminata × balbisiana) - Windari, Trisna; Yurliasni, Yurliasni; Mariana, Elmy; Marpaung, Deva Aryana; Jinnani, Rida Raihatil (Asian Journal of Environmental Research, 2025)
Probiotics  are  microbes  that  are  alive  and  beneficial  to  their  hosts.  Some  probiotic  bacteria  are  Lactobacillus  plantarum  and  Lactobacillus  acidhopillus.  The  performance  of  these  two  bacteria  will  be  optimal  if  prebiotics  are  added  as  a  source  of  nutrition,  namely  kepok  banana  (Musa  acuminata  ×  balbisiana).  The  aim  of  the  research  was  to  analyze  the  comparative  physicochemical  and  microbiological  properties  of  fermented  goat's  milk  using  Lactobacillus  plantarum  and  Lactobacillus  acidhopillus  with  prebiotic  kepok  banana  puree  (Musa  acuminata  ×  balbisiana).  The  study  used  a  completely  randomized  design  with  a  factorial  pattern,  factor  A  percentage  of  kepok  banana  puree  P1=  5%  kepok  banana  puree,  and  P2=  15%  kepok  banana  puree,  factor  B  V1=  Lactobacillus  plantarum  (5%)  and  V1=  Lactobacillus  acidhopillus  (  5%),  done  3  times  repetition.  The  results  of  the  research  were  that  adding  15%  kepok  banana  puree  to  Lactobacillus  plantarum  was  better  at  increasing  lactic  acid  levels  and  bacterial  growth  in  the  Total  Plate  Count,  and  15%  kepok  banana  puree  to  Lactobacillus  acidophilus  was  better  at  lowering  pH,  increasing  protein  levels,  reducing  syneresis  and  increase  the  viscosity  value.  The  conclusion  of  this  research  is  that  the  use  of  15%  can  improve  the  performance  of  Lactobacillus  plantarum  and  Lactobacillus  acidhopillus,  and  in  general  all  research  parameters  are  still  within  the  Indonesian  National  Standard  range. These findings contribute to the advancement of food science and microbiology by demonstrating the potential of kepok banana puree in improving the quality of goat milk-based probiotic products.